PELATIHAN PEMBUATAN MEDIA PEMBELAJARANDARI BAHAN ALAM PADA GURU RA BINAANAPRASADI DESA SUKASARI - Suci Purwati; Widya Masitah (JOURNAL OF COMMUNITY DEDICATION, 2024)
In the learning process of early childhood, it does not only require reading, writing, and arithmetic, but they also need learning media in the process of implementing their learning. The training on making learning media for teachers of Raudhatul Athfal Bina Anaprasa in Sukasari village was carried out due to the lack of knowledge about learning media from natural materials in RA Bina Anaprasa teachers. This is because teachers are not able to use natural materials that can be used as learning media. The purpose of this service is to improve and export the creativity possessed by an early childhood education teacher in makinglearning media using natural basic materials. This service method and design consists of several stages, including the initial stage, implementation, and finally monitoring and evaluation. The end result of this service is that the teachers turn out to have high creativity, especially they are also able to combine the available natural basic materials with other materials to further add creativity values to the creation of the learning media they make. This training in making learning media must be carried out continuously so that teachers are able to develop their competencies to be more optimal.